Thirty years of HIV pregnancies in French Guiana: prevention successes and remaining obstetrical challenges - Nacher, Mathieu; Blanc, Julie; Rabier, Sebastien; Lucarelli, Aude; Adenis, Antoine; Basurko, Celia; Louis, Alphonse; Dotou, Dominique; Leneuve, Malika; Osei, Lindsay; Elenga, Narcisse; Hcini, Najeh (Frontiers in Global Women's Health, 2024)
Introduction In a context of high HIV prevalence, poor pregnancy follow-up, frequent poverty, preeclampsia, and preterm delivery, we aimed to describe the characteristics and outcomes of pregnancies among women living with HIV in French Guiana. Methods A retrospective cohort study was conducted on HIV-infected pregnancies enrolled between January 1st 1992 to 31st July 2022. Overall, there were 1,774 pregnancies in 881 women living with HIV. Results For 75.1% of pregnancies, the HIV diagnosis was already known before pregnancy and in 67.6% of women, HIV follow-up predated pregnancy. Nearly half of women, 49.6%, only had one pregnancy since having been diagnosed with HIV. Although most women received antiretroviral therapy during pregnancy, for those with the available information we found only 48.5% had an undetectable viral load at delivery. Overall, 15.3% of pregnancies ended with an abortion. There were a total of 110 newborns infected with HIV representing an overall transmission rate of 6.2% (110/1,771). Between 1993 and 2002, the transmission rate was 34%, between 2003 and 2012 it was 1.3%, and between 2013 and 2022 it was 0.7%. Overall, in Cayenne, since 2008, 106 of 581 HIV–infected pregnancies (18.2%) with available information were premature before 37 weeks of pregnancy; of these, 33 (5.7%) were very preterm deliveries and 73 (13.3%) were late preterm deliveries. Over time, in Cayenne, preterm delivery declined significantly. Conclusions The present study emphasizes that, despite spectacular progress in reducing mother to child transmission, pregnancy outcomes among women living with HIV are still preoccupying with high incidence of preterm delivery and low birth weight. Teasing out what fraction is linked to HIV and what fraction is linked to social precariousness and poor follow-up was not possible in this study. Despite the high incidence of very preterm delivery recent progress suggests that coordination efforts to improve follow-up may also have improved obstetrical outcomes.